The hematopoietic stroma - Nardi,N.B. (1999)
All blood cells are derived from a small common pool of totipotent cells, called hematopoietic stem cells. The process is strictly regulated by the hematopoietic microenvironment, which includes stromal cells, extracellular matrix molecules and soluble regulatory factors. Several experimental in vitro assays have been developed for the study of hematopoietic differentiation, and have provided valuable information on the stroma, which includes, among other cell types, macrophages, fibroblasts, adipocytes, and endothelial cells. The composition, ontogeny, and function in physiological as well as pathological conditions of stroma are discussed.